FEATURES DIAGNOSTIC FINDING IN DERMATOMYOSITIS (CLINICAL OBSERVATION) - A. E. Shklyaev; S. G. Zamyatina; Yu. V. Gorbunov; L. V. Ivanova (Архивъ внутренней медицины, 2017)
In connection with the polymorphism of clinical manifestations of dermatomyositis, patients in the onset of the disease can apply to doctors of any specialty. However, the statement of this diagnosis causes considerable difficulties for practical doctors who do not work in the field of rheumatology. To a large extent this is due to the fact that inflammation of the muscle tissue can have not only an autoimmune origin, but also be observed with a variety of infections and intoxications. Diagnosis of dermatomyositis is associated with the need to eliminate tumor processes in the body, accompanying it in 20% of cases. The article presents a clinical case of subacute dermatomyositis, which occurred in a man 49 years after massive insolation against the background of photosensitization with fluoroquinolones in the treatment of prostatitis. After detecting a significant increase in the level of serum “muscle” enzymes and electromyographic signs of inflammatory myopathy, a patient with characteristic progressive symmetrical muscle weakness of the proximal limb and skin changes was diagnosed with primary idiopathic dermatomyositis with the activity of III degree. Diagnostic search required the exclusion of infectious and neoplastic diseases. Timely formulation of the diagnosis made it possible in time to prescribe immunosuppressive therapy with glucocorticosteroids, achieving a decrease in the activity of the disease and improving the prognosis.